The Development of Al-Qur'an-Based Science Magazine on Human Movement System Material for Class VIII SMP/MTs Students - Hasanah, Inta Niatul; Susanti, Laily Yunita (Rausyan Fikri Journal of Islamic Studies, 2024)
This research was conducted to develop a Qur'an-based Science magazine on the human movement system material for class VIII SMP/MTs students. The research objectives are to describe the validation of the Qur'an-based science magazine on the Human Movement System material for class VIII SMP/MTs students and to describe the students' responses to the Qur'an-based science magazine that was developed. This research is a research and development research using the 4-D Thiagarajan development model with the research stages of define, design, develop and disseminate. The results of this research are in the form of a science magazine based on the Qur'an on the Human Movement System material for class VIII SMP/MTs which is used as a learning support book with a material expert test validity level of 88.75%, religious validity of 85%, media validity by 97.14% and users (teachers) by 90.30% which means science magazines are included in a very valid category to be used as a supporting book. Then the results of the students were 90, 96% with a sample of 6 students in class VIII, and the results of the large-scale student response test of 90.66% with a sample of 30 students in class VIII. These results indicate that the magazine is included in the very attractive category for the development of a science magazine based on the Koran on the Human Movement System material for SMP/MTs Class VIII students.